Application of the ELECTRE III Method at the Moroccan Rural Electrification Program - Fatima Zahra El Mazouri; Mohammed Chaouki Abounaima; Khalid Zenkouar; Ahmed El Hilali Alaoui (International Journal of Electrical and Computer Engineering (IJECE), 2018)
As part of the integrated strategy of the Moroccan state aimed at the social and economic development of the Moroccan rural community, an electrification program has been in place since the 90s. This program, called PEGR, has for main objective the improvement of the electrification rate for the national rural world. Given the large number of villages to be electrified and the colossal budget that will induce, several criteria have been retained to objectively distinguish the villages with the highest priority for electrification. Given the nature of this problem to be solved, which is a multicriteria decision aid problem, we propose in this article to use the multicriteria aggregation method ELECTRE III to rank the villages from the highest priority to the lowest priority for the electrification.